Pengaruh Social Commerce, Brand Image, dan Brand Trust Terhadap Minat Beli Produk Aerostreet - Maheswara, Fabhian Yongga; Satoto, Shinta Heru (Jurnal Manajemen, 2023)
This study aims to analyze the Influence of Social Commerce, Brand Image, and Brand Trust on Buying Interest of Aerostreet Products. This research is a survey research with a data collection tool using a questionnaire which is disseminated through google form. The population of this research is followers of the official account TikTok Aerostreet. The data used is primary data obtained from the answers of 100 respondents with the purposive sampling method. The data analysis technique used is multiple linear regression. The results of this study can be concluded as follows: 1) Social Commerce has a positive and significant effect on buying interest of Aerostreet products in official account TikTok Aerostreet, 2) Brand Image has a positive and significant effect on buying interest of Aerostreet products in official account TikTok Aerostreet, dan 3) Brand Trust has a positive and significant effect on buying interest of Aerostreet products in official account TikTok Aerostreet.